The other side of innovation : solving the execution challenge - Govindarajan, Vijay. (Harvard Business School Pub., 2010)
The authors reveal how to execute an innovation initiative. Regardless of the type of initiative, the crux of the challenge is that business organizations are not designed for innovation; they are designed for ongoing operations. And there are deep and fundamental conflicts between the two.